2017
DOI: 10.1002/zaac.201700209
|View full text |Cite
|
Sign up to set email alerts
|

N‐Heterocyclic Phosphenium Dihalido‐Aurates: On the Borderline between Classical Coordination Compounds and Ion Pairs

Abstract: Abstract. 2-Bromo-and 2-chloro-1,3,2-diazaphospholenes react with (tht)AuCl to afford isolable N-heterocyclic phosphenium (NHP) dihalido-aurates, which were characterized by analytical and spectroscopic data and in one case by a single-crystal X-ray diffraction study. The T-shaped metal coordination sphere found in the crystal consists of a pseudo-linear AuX 2 unit that is perturbed by a weakly bound NHP unit. DFT studies indicate that the subunits interact mainly through electrostatic and dispersion forces, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, it has been shown that NHP + cations can bind to metals in a pyramidal geometry, indicative of a stereochemically active lone pair that is not engaged in bonding to the metal (Figure 1). [11][12][13] Our group has shown that installing an NHP + fragment in a rigid diphosphine pincer ligand framework (PPP) destabilizes the singlet ground state of the NHP + upon coordination to a metal, facilitating reduction to an N-heterocyclic phosphido (NHP -) state. Complexes bound to NHPfragments have longer, more covalent metal-P NHP bonds while the central phosphorus adopts a pyramidal geometry.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that NHP + cations can bind to metals in a pyramidal geometry, indicative of a stereochemically active lone pair that is not engaged in bonding to the metal (Figure 1). [11][12][13] Our group has shown that installing an NHP + fragment in a rigid diphosphine pincer ligand framework (PPP) destabilizes the singlet ground state of the NHP + upon coordination to a metal, facilitating reduction to an N-heterocyclic phosphido (NHP -) state. Complexes bound to NHPfragments have longer, more covalent metal-P NHP bonds while the central phosphorus adopts a pyramidal geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Such complexes are currently known for most transition metals. There are several reports on complexes when phosphenium cation acts as an acceptor 27,28 only and phosphide derivatives formed by the oxidation of metal centre. [29][30][31][32][33] The most studied methods for preparing complexes with NHP + are anion (halogen) abstraction from phosphorus, 21,[34][35][36][37][38][39] metathesis between carbonylate and halogeno-NHP, 18,29,[40][41][42][43][44] oxidative additions to a metal 30,33,[45][46][47] and coordination of a stable phosphenium cation to a metal fragment.…”
Section: Introductionmentioning
confidence: 99%
“…Such complexes are currently known for most transition metals. There are several reports on complexes when phosphenium cation acts as an acceptor 27,28 only and phosphide derivatives formed by the oxidation of metal centre. 29–33…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18][19][20] Additionally, in some cases phosphenium ions display the ability to act as σ-accepting (Z-type) ligands. [21][22][23] While N-heterocyclic nitrenium ions require the presence of additional donor groups in a chelating ligand to bind to a transition metal, the heavier homologous phosphenium ions can act as monodentate ligands. A similar example are sulfonium ions, which can be regarded as isoelectronic and thus cationic analogues of tertiary phosphines.…”
Section: Introductionmentioning
confidence: 99%